If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1d = a Solving X + -1d = a Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'd' to each side of the equation. X + -1d + d = a + d Combine like terms: -1d + d = 0 X + 0 = a + d X = a + d Simplifying X = a + d
| 3z-2y=12 | | Z+5y=10 | | m/60=26 | | 134=9n+2(4n-1) | | Ln^2=11 | | 2z+y=12 | | 13/17=v/10 | | sen3x=1/2 | | 7x-5(-7x+6)=-240 | | 4x+3y-z=17 | | 6z-2y=8 | | -5(1+9v)=310 | | 10x+30=20x+20 | | 6x^2+35=68 | | 9z-12y=9 | | -504=3(11x+4)+10x | | 3z-4y=3 | | -7(6)(-1)= | | 35k=1925 | | 5x-57-2x=63 | | 4x^2-28-32=0 | | 18d^5+6d^4+9d^3= | | 3+4Inx=5 | | -7n-10=60 | | X+9=90 | | 2x+2y+z=11 | | 1-17x+37x=1 | | 19-11/-2 | | 5+2x=-20+5x | | 1/8=z^(6x) | | -14x-25-22=79 | | 14x-25-22=29 |